2014
DOI: 10.3168/jds.2014-8391
|View full text |Cite
|
Sign up to set email alerts
|

Diet effects on glucose absorption in the small intestine of neonatal calves: Importance of intestinal mucosal growth, lactase activity, and glucose transporters

Abstract: Colostrum (C) feeding in neonatal calves improves glucose status and stimulates intestinal absorptive capacity, leading to greater glucose absorption when compared with milk-based formula feeding. In this study, diet effects on gut growth, lactase activity, and glucose transporters were investigated in several gut segments of the small intestine. Fourteen male German Holstein calves received either C of milkings 1, 3, and 5 (d 1, 2, and 3 in milk) or respective formulas (F) twice daily from d 1 to d 3 after bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
36
2
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(44 citation statements)
references
References 58 publications
4
36
2
2
Order By: Relevance
“…Unlike the healthy liver [36], the intestine responds to changes in workload primarily by adjusting its cellularity [11]. In fact, our histomorphometrical results in the liver are in line with findings in the small intestine [15, 35] as both indicate that improved feed efficiency is accompanied by a higher metabolic demand on these visceral organs. Interestingly, a study by Colnot et al [37] on glucose absorption in the small intestine of neonatal calves demonstrated the primary role of the mucosal growth to trigger the intestinal metabolism of glucose.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Unlike the healthy liver [36], the intestine responds to changes in workload primarily by adjusting its cellularity [11]. In fact, our histomorphometrical results in the liver are in line with findings in the small intestine [15, 35] as both indicate that improved feed efficiency is accompanied by a higher metabolic demand on these visceral organs. Interestingly, a study by Colnot et al [37] on glucose absorption in the small intestine of neonatal calves demonstrated the primary role of the mucosal growth to trigger the intestinal metabolism of glucose.…”
Section: Discussionsupporting
confidence: 86%
“…Similarly, Steinhoff-Wagner et al [35] found that breeds of cattle with higher growth rates and superior feed efficiency had greater cellularity in the small intestine compared with the cattle breeds with lower growth rates. Unlike the healthy liver [36], the intestine responds to changes in workload primarily by adjusting its cellularity [11].…”
Section: Discussionmentioning
confidence: 99%
“…High consumption of available carbohydrates, such as glucose, sucrose, lactose, or fructose, is postulated to overwhelm absorptive mechanisms of the intestine, resulting in increased luminal sugar concentrations that are then used as an energy source by the microbiota 56 . In support of this hypothesis, IBD patients often have evidence of fructose malabsorption or lactose intolerance 57 .…”
Section: Carbohydratesmentioning
confidence: 99%
“…Steinhoff‐Wagner et al. () comparing 4‐day‐old calves fed with colostrum or formula in the first 4 days of life also found greater villus circumference, area and height and smaller crypt depth in calves fed colostrum. Considering intestinal cell renewal within three to 4 days (Sangild, ), the results of Yang et al.…”
Section: Discussionmentioning
confidence: 95%
“…() and Steinhoff‐Wagner et al. () indicate the possibility of a lower rate of cell turnover in an attempt to maintain a first generation of epithelial cells that have the ability to absorb macromolecules, revealing that different mechanisms regulate the development and growth of the intestinal epithelium.…”
Section: Discussionmentioning
confidence: 99%